Basketball basics - Morris, Greggory; Engelland, Timothy; Jones, Brent (Englewood Cliffs, N.J. : Prentice-Hall, 1976)
Discusses jumping and shooting strategy, shape-up and maintenance exercises, and good nutrition for the seven to ten year old who wants to play basketball but isn't old enough for an organized team.
Includes index.
1
Keywords: Basketball -- Juvenile literature